Representações sociais do tráfico de drogas e da violência: concepções de moradores de favelas e de áreas abastadas - Maciel, Karen Rodrigues (2023)
The present work aimed to look into the social representations of drug dealing and violence for residents of social vulnerability zone and wealthy areas. It was also desired to realize a comparative analysis of such representations, identifying possible similarities and dissonances. For this, the Theory of Social Representations was used as a guiding theory. The method is a qualitative research and the participants were twenty residents of Grande Vitória, ten residents of social vulnerability zone and wealthy areas, counting as an inclusion criterion residing for five years or more in the region, or having been born in the place and be of age. The instrument of this research deals with a semi-structured interview. Data analysis was based on the Content Analysis proposal. The results confirm that the influences of the field to which one is a part also reverberate in the social representations of the residents. In addition, they face specific experiences regarding violence in society and drug trafficking. It is expected that after the interlocutions between the data obtained and the basic theories, it will be possible to contribute to the scientific field of representations, as well as to bring reflections on the specificities of illegal drug trafficking and violence, and social classes.